2009
DOI: 10.1074/jbc.m109.035899
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-C Motif) Ligand 2 Engages CCR2+ Stromal Cells of Monocytic Origin to Promote Breast Cancer Metastasis to Lung and Bone

Abstract: Metastatic spread of cancer to distant vital organs, including lung and bone, is the overwhelming cause of breast cancer mortality and morbidity. Effective treatment of systemic metastasis relies on the identification and functional characterization of metastasis mediators to multiple organs. Overexpression of the chemokine (C-C motif) ligand 2 (CCL2) is frequently associated with advanced tumor stage and metastatic relapse in breast cancer. However, the functional mechanism of CCL2 in promoting organ-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
184
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(198 citation statements)
references
References 56 publications
12
184
0
2
Order By: Relevance
“…Over the past years, accumulating evidence has demonstrated novel roles for chemokines and their receptors in regulating biology of the malignant tumors, including metastasis [2][3][4]. Determination of such a predictive molecular marker that is correlated with lymph node metastasis might be important in elucidating the mechanism of metastasis and aid in the personalized theraphy of breast cancer.…”
mentioning
confidence: 99%
“…Over the past years, accumulating evidence has demonstrated novel roles for chemokines and their receptors in regulating biology of the malignant tumors, including metastasis [2][3][4]. Determination of such a predictive molecular marker that is correlated with lymph node metastasis might be important in elucidating the mechanism of metastasis and aid in the personalized theraphy of breast cancer.…”
mentioning
confidence: 99%
“…Furthermore, in the present study, Smith and colleagues (7) focused only on IL-6, although they also observed that deletion of Ido1 also blunted MCP-1 levels. It is known that MCP-1 (CCL2), together with CCR2, plays a role in the recruitment of immune cells to the tumor microenvironment and also increases the migration of tumor and stromal cells that express CCR2 (10). Moreover, CCL2 expression by tumor or stromal cells and CCR2 + macrophage infi ltration correlates with poor prognosis and metastasis in human breast cancer (11).…”
Section: Open Questionsmentioning
confidence: 99%
“…In particular, inflammatory chemokines, such as CCL2 and CCL5, are associated with poor prognosis of breast, pancreas and colon cancer due to metastasis, although the mechanisms of action remain under investigation [14][15][16]. CCL2-and CCL5-mediated recruitment of monocytes has been demonstrated to facilitate metastasis for different cancer types [8,12,17]. Recently, we have demonstrated that CCL2 does not only recruit monocytes to the sites of metastasis but, more importantly, enables cancer cell extravasation [13].…”
Section: Future Oncology Part Ofmentioning
confidence: 99%
“…Depending on the stage, cancer patients display a high number of circulating tumor cells and metastasis, therefore a therapy aimed at preventing cancer cell extravasation may strongly reduce the risk of new metastasis, but may not prevent the development of small, already established ones. Nevertheless, accumulating experimental evidence strongly suggests that the interference in cancer cell communication with the microenvironment (e.g., through CCL2) leads to attenuation of metastasis in a number of animal models [8,13,17,18]. Based on this preclinical evidence, two clinical trials have been initiated, evaluating the safety and efficacy of blocking both CCL2 and CCR2 in metastatic patients [101,102].…”
Section: "Efficient Inhibition Of Established Ormentioning
confidence: 99%